Business strategies and management accounting in response to climate change risk exposure and regulatory uncertainty. Issue 1 (January 2017) - Bui, Binh; de Villiers, Charl
Abstract: This study aims to theorise and foster a better understanding of the strategies organisations adopt to respond to the risks and opportunities emerging from changing government climate change policies and the supporting management accounting adopted. Data include interviews and archival documents from five New Zealand electricity generators. We construct a theoretical framework that links climate change risks and opportunities to strategic responses. Climate change risk exposure increased during the period due to changes in the estimation/perception of climate change risks, market opportunities and regulatory uncertainty. Organisations' strategies changed in response, moving from a stable strategy to different combinations of anticipatory, proactive, and creative strategies, and finally regressing to a reactive strategy. Carbon management accounting changed to support the new strategy adopted in each time period. Long term physical and monetarised accounts for sustainability and extensive use of carbon information were prevalent during periods when the companies employed a proactive or creative strategy. In contrast, short-term physical accounts for unsustainability and limited use in decision-making were observed when the companies adopted stable, anticipatory or reactive strategies. Regulatory uncertainty was found to be the major constraint to a proactive strategy and carbon management accounting development in response to climate change.